(untitled) (City: History, Culture, Society, 2021)
The Soviet past in the modern Ukrainian society continues to function in the continuum “Our – Alien”. The dichotomy in the perception of the past cannot provoke discussions and conflicts in the field of memory policy. The article discusses the memory of Soviet monuments on the Heroe’s Alley in Chernihiv in the aftermath of independence. Based on a local example, one can trace the reception of decommunization processes in memory of locals. According to this, see attitude to monuments that are associated with the Soviet period. The city has preserved a significant number of Soviet monuments since independence. Monuments continued to perform their function as they did in Soviet times: on traditional Soviet holidays, gatherings were formed around them, rallies were held. The city continued to live in the historical narrative set by the Soviet regime. Memory or/and amnesia? These are words that can describe a debate around Heroe’s Alley for 28 years. From time to time, the Alley becomes a field for mnemonic actors to fight for the right to “own” this place. However, it eventually disappears from public discourse, thus becoming a usual alley like any other Ukrainian city has. Unpublished materials of the State Archives of Chernihiv Region were used to write the article. As the research topic includes a recent chronological period, Internet resources such as site “Podiyi i komentari: Chernihiv Region”, “Vysokyi Val (VAL.UA)” and “Svoboda.FM” were used during the writing of the article. These information resources specialize in covering events of Chernihiv region, and therefore are an important center for analysis of memory policy regarding monuments on the Alley of Heroes.